Altered visual and somatosensory feedback affects gait stability in persons with multiple sclerosis - Craig, Jordan J. (Hum Mov Sci, 2019)
Persons with multiple sclerosis (PwMS) often report problems due to sensory loss and have an inability to appropriately reweight sensory information. Both of these issues can affect individual’s ability to maintain stability when walking under challenging conditions. The purpose of the current study was to determine how gait stability is adapted when walking under challenging sensory conditions where vision and somatosensation at the feet is manipulated. 25 healthy adults and 40 PwMS (15 fallers, 25 non-fallers) walked on a treadmill at their preferred normal walking speed under 3 conditions: normal walking, altered vision using goggles that shifted visual field laterally, and altered somatosensation using shoes with compliant foam soles. Inertial measurement united recorded acceleration at the lumbar and right ankle, and acceleration variability measures were calculated including root mean square (RMS), range, sample entropy (SaEn), and Lyapunov exponents (LyE). A gait stability index (GSI) was calculated using each of the four variability measures as the ratio of lumbar acceleration variability divided by foot acceleration variability in the frontal and sagittal planes. The sagittal and frontal GSI(RMS) were larger in the somatosensory condition compared to the normal and visual conditions (p < 0.001). The frontal GSI(SaEn) was greater in the visual condition compared to the somatosensory condition (p=0.021). The frontal and sagittal GSI(LyE) was greater in the somatosensory condition compared to the normal and visual conditions (p < 0.002). The current study showed that HC, MS non-fallers and MS fallers largely adapted to altered sensory feedback during walking in a similar manner. However, MS faller subjects may be more reliant on visual feedback compared to MS non-fallers and HC subjects.